2011
DOI: 10.1111/j.1460-9592.2011.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Substantial postoperative pain is common among children undergoing laparoscopic appendectomy

Abstract: These preliminary data suggest that substantial postoperative pain is common in children undergoing laparoscopic appendectomy. More studies of postoperative pain outcomes among children undergoing laparoscopic appendectomy and other common pediatric surgical procedures are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 29 publications
4
29
1
Order By: Relevance
“…If a child was sleeping during the first 15min of PACU admission, the nurses recorded a pain score of zero. This is consistent with routine clinical practice and has been previously reported (13). Furthermore, the primary objective of this report was PACU rescue analgesic requirement, hence cross-sectional (first or arousal and the highest recorded pain scores) were noted for all patients.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…If a child was sleeping during the first 15min of PACU admission, the nurses recorded a pain score of zero. This is consistent with routine clinical practice and has been previously reported (13). Furthermore, the primary objective of this report was PACU rescue analgesic requirement, hence cross-sectional (first or arousal and the highest recorded pain scores) were noted for all patients.…”
Section: Methodssupporting
confidence: 93%
“…Several potential predictors of early postoperative pain following ambulatory surgical procedures have been identified (1113). However, patient-specific predictors of clinically important PACU pain following ambulatory surgery in children have not been comprehensively determined.…”
Section: Introductionmentioning
confidence: 99%
“…We found similar results for the initial admission, but we also found a higher re‐presentation rate following laparoscopic appendicectomy for uncomplicated appendicitis. It is possible that children undergoing laparoscopic appendicectomy recover more slowly than is recognised, and that the discomfort of laparoscopy may take time to subside 14 . Children have smaller abdominal cavities than adults, and insufflation with carbon dioxide is often required for a laparoscopic appendicectomy; the additional stretching of the anterior abdominal wall and diaphragm can cause post‐operative discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tomecka et al (13) found that children who underwent LA had a substantial pain at 1: 3 ratio on the first, and 1: 5 on the second postoperative day. Therefore, the development of pain therapy regimens that can be reliably applied to the pediatric patients who have undergone OA as well as to children who are treated with LA is an important need.…”
Section: Discussionmentioning
confidence: 99%